The words as magic as the music : Rock journalist Lillian Roxon’s discourses of rock music and rock music culture - Vahtera, Jasmin (My University, 2023)
In this thesis, I study the discourses of rock music in the writings of music journalist Lillian Roxon (1932–1973). Roxon was a pioneering journalist, gossip columnist, a chronicler and non-fiction writer. She left Australia, Brisbane for New York at the end of the 1950s. Roxon published Lillian Roxon’s Rock Encyclopedia in 1969 which was a comprehensive work about rock musicians and bands from the 1950s to 1960s. The encyclopedia made her famous and in its wake, she was asked to become a rock columnist for a major newspaper New York Sunday News. In this thesis, I will focus on Roxon’s column on rock music The Top of Pop, which ran weekly in the New York Daily News Sunday edition New York Sunday News from 1970 to 1973. The column was one of the first rock columns in a newspaper written by a female rock critic. In The Top of Pop Roxon wrote extensively and bravely on various topics related to rock music culture. She often paid attention to aspects that other media had not necessarily paid attention to, amongst others gender in rock music culture. Roxon was an influential critic and journalist of her time but still, she has been left in the shadows of rock music history. The theoretical background of the study is located to Anglo-American music criticism, rock journalism, cultural study of music and gender in rock journalism. As a method for my study, I have used close reading of the columns and critical discourse analysis (CDA). This way I have formed the categories of different discourses I have analysed from the columns. Even though there are dozens of different themes in the columns certain topics can be differentiated. I have divided my thesis’ analysis chapters into four different categories according to the themes. These are age, time and nostalgia, music and sound, gender and rock stars. According to my study, Roxon did maintain and reproduce features that were (and still are) commonplace in rock music culture such as the mystification of rock stars but she also pondered and brought forward less talked about themes such as gendered issues in the rock music scene. In Roxon’s own discourses rock was most of all an ideology that divided people into us and them. Equally, age was seen as an ideology too. In The Top of Pop Roxon wanted to create a picture that age does not determine, for example, whether you can participate in rock culture or not. Everyone who was involved in rock music culture could be seen as young. It was a question of choice. In addition, Roxon pondered, for instance, the gender discourses of rock music. She wanted to improve the status of women in rock music culture. Rock stars were the stars of the column and Roxon wrote about them from many different angles. She admired them, poked fun at them, mystified them. According to my study, for Roxon, the most important themes in both rock music and its performers were authenticity, transcendence, seriousness and decadence. The Top of Pop created its own world in the rock music scene of the 1970s in New York. Through her Rock Encyclopedia and The Top of Pop Roxon became an influential authority in rock music.

Tässä opinnäytetyössäni tutkin rockmusiikin diskursseja musiikkitoimittaja Lillian Roxonin (1932–1973) kirjoituksissa. Roxon oli uraauurtava toimittaja, juorukolumnisti, kronikoitsija ja tietokirjailija. Hän muutti Australian Brisbanesta New Yorkiin 1950-luvun lopulla. Roxon julkaisi vuonna 1969 Lillian Roxon's Rock Encyclopedian, joka oli kattava teos 1950–1960 -lukujen rockmuusikoista ja -yhtyeistä. Tietosanakirja teki Roxonista kuuluisan, ja sen myötä häntä pyydettiin rockkolumnistiksi New York Sunday News -sanomalehteen. Tässä opinnäytetyössä keskityn Roxonin rockmusiikkia käsittelevään kolumniin The Top of Pop, joka julkaistiin viikoittain New York Daily News -lehden sunnuntainumerossa New York Sunday News vuosina 1970–1973. Kolumni oli yksi ensimmäisistä sanomalehdessä julkaistuista naisen kirjoittamista rock-kolumneista. The Top of Popissa Roxon kirjoitti laajasti ja rohkeasti erilaisista rockmusiikkikulttuuriin liittyvistä aiheista. Hän kiinnitti usein huomiota asioihin, joihin muut mediat eivät olleet välttämättä kiinnittäneet huomiota, kuten esimerkiksi sukupuoleen rockmusiikkikulttuurissa. Roxon oli aikansa vaikutusvaltainen rockkriitikko ja toimittaja, mutta silti hän on jäänyt rockmusiikin historian ja historiantutkimuksen varjoon. Tutkimuksen teoreettinen tausta sijoittuu angloamerikkalaisen musiikkikritiikin perinteeseen, rockjournalismiin, kulttuuriseen musiikintutkimukseen ja sukupuolen tutkimiseen rockjournalismissa. Tutkimukseni menetelmänä olen käyttänyt lähilukua ja kriittistä diskurssianalyysiä (CDA). Vaikka kolumneissa käsitellään kymmeniä eri teemoja, tietyt aiheet voidaan erottaa isommiksi pääkategorioiksi. Olen jakanut opinnäytetyöni analyysiluvut neljään eri kategoriaan teemojen mukaan. Nämä ovat ikä, aika ja nostalgia, musiikki ja ääni, sukupuoli ja rocktähdet. Tutkimukseni mukaan Roxon säilytti ja toisti rockmusiikkikulttuurissa arkipäiväisiä piirteitä, kuten rocktähtien mystifiointia, mutta hän myös pohti ja toi esiin vähemmän puhuttuja teemoja, kuten rockmusiikkiin liittyviä sukupuolikysymyksiä. Roxonin omissa diskursseissa rock oli ennen kaikkea ideologia, joka jakoi ihmiset meihin ja heihin. Myös ikä nähtiin ideologiana. The Top of Popissa Roxon halusi luoda kuvan siitä, että ikä ei määrää esimerkiksi sitä, kuka saa osallistua rockkulttuuriin. Kaikki, jotka olivat mukana rock-musiikkikulttuurissa, voitiin nähdä nuorina. Kyseessä oli valinta. Lisäksi Roxon pohti muun muassa rockmusiikin sukupuolidiskursseja. Hän halusi parantaa naisten asemaa rock-musiikkikulttuurissa. Kolumnin päätähtiä olivat rocktähdet, joista Roxon kirjoitti monista eri näkökulmista. Hän ihaili, pilkkasi ja mystifioi heitä. Tutkimukseni mukaan Roxonille tärkeimmät teemat sekä rockmusiikissa että sen esittäjissä olivat aitous, transsendenttius, vakavuus ja dekadenssi. The Top of Pop loi oman maailmansa 1970-luvun rockmusiikkiskenessä New Yorkissa. Rocktietokirjan ja The Top of Popin myötä Lillian Roxonista tuli vaikutusvaltainen auktoriteetti 1970-luvun rockmusiikkipiireissä.
Keywords: rock music culture, rock journalism, rock critic, rock stars, gender, nostalgia, feminism, 1970s rock music, 1960s rock music, rock and roll, women in rock, women in rock journalism, discourses